International Court of Justice (ICJ): The Role of the International Court of Justice in Developing International/Global Law: A Survey of ICJ Decisions 2022–2023 - Kolb, Robert; Hêche, Aymeric (Oxford University PressNew York, 2024)
The period 1 August 2022–July 2023 is characterized by an intense activity. The International Court of Justice’s docket has never been so full, and the trend is clearly upwards. Four judgments were issued, the International Court of Justice ruled on four applications for provisional measures, and numerous hearings were conducted. The judgments were very different in scope and subject matter: law of international watercourses was at the heart of Chile v. Colombia, interpretation of treaties in Iran v. United States, the “Monetary Gold” principle in Guyana v. Venezuela, and the existence of customary international law in Nicaragua v. Colombia.
Keywords: modification of provisional measures; declaration of Intervention; interpretation of treaties; customary international law; good administration of justice